2016
DOI: 10.2174/1568026616666160530153233
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2-a]pyridine Scaffold as Prospective Therapeutic Agents

Abstract: Imidazo[1,2-a]pyridine is one of the most potential bicyclic 5-6 heterocyclic rings that is recognized as a "drug prejudice" scaffold due to its broad range of applications in medicinal chemistry such as anticancer, antimycobacterial, antileishmanial, anticonvulsant, antimicrobial, antiviral, antidiabetic, proton pump inhibitor, insecticidal activities. This scaffold has also been represented in various marketed preparations such as zolimidine, zolpidem, alpidem. Therefore, several attempts were made to carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…The unique loss of heparan sulfates was correlated with the degradation of the glycocalyx and the activation of heparanase TNF‐α‐heparan‐specific sulfate glucuronidase. [ 56,57 ]…”
Section: The Egx In the Pathophysiologymentioning
confidence: 99%
“…The unique loss of heparan sulfates was correlated with the degradation of the glycocalyx and the activation of heparanase TNF‐α‐heparan‐specific sulfate glucuronidase. [ 56,57 ]…”
Section: The Egx In the Pathophysiologymentioning
confidence: 99%
“…Compounds with the imidazo[1,2-a]pyridine scaffold exhibit a plethora of biological activities, including acting as receptor ligands, anti-infectious agents, enzyme inhibitors etc. as well as being potential nitrogen heterobicycle therapeutic agents, as described by recent studies (Goel et al, 2016;Deep et al, 2017;Kuthyala et al, 2018). On the other hand, compounds containing the 1,3-dithiolan-2-ylidene moiety have been found to exhibit valuable pharmacological activities, including use as potent broad-spectrum fungicides (Tanaka et al, 1976, Wang et al, 1994, antitumor agents (Huang et al, 2009), potent cephalosporinase inhibitors (Ohya et al, 1982) and anti-HIV agents (Nguyen-Ba et al, 1999;Besra et al, 2005).…”
Section: Chemical Contextmentioning
confidence: 99%
“…5,6 Some of them are well-known commercialized drugs with sedative, anti-hypnotic and anti-psychotic effects, such as Alpidem, Zolpidem and Olprinone. 7 Recent investigations showed that imidazo [1,2-a]pyridines are promising drug candidates in cancer treatment. 8,9 The photophysical properties of these heterocyclic scaffolds have also been investigated [10][11][12] and their potential as fluorescent probes 13 and fluorescent metal sensors has been explored.…”
Section: Introductionmentioning
confidence: 99%